Peran good corporate governance, profitabilitas, size dan likuiditas dalam mengungkap corporate social responsibility - Dian Yuni Damayanti (STIE Perbanas Surabaya, 2017)
Corporate Social Responsibility (CSR) is one of several corporate responsibilities for stakeholders. The Company will disclose its social responsibility practices so that the contributions they had can be recognized by the stakeholders. This study aims to determine the effect of Good Corporate Governance (GCG), profitability, size, and liquidity to CSR disclosure. GCG is measured using independent commissioners, managerial ownership, and institutional ownership. This study uses a manufacturing company in Indonesia as the sample in the period 2012-2015. The sampling technique used is purposive sampling method. The analysis technique used is multiple regression analysis. The results showed that independent commissioners, managerial and liquidity ownership had no effect on CSR disclosure, while institutional ownership, profitability and firm size had a significant positive effect on CSR disclosure.